Bird Species in the Wetlands of Barito Kuala District, Indonesia - Soendjoto, Mochamad Arief; Fahlevi, Muhammad Mirza; Winarti, Atiek (BIOEDUKASI, 2024)
There have been no publications on birds found in the wetlands of Barito Kuala District. If anything, the prevailing assumption is that many water birds are found in these wetlands. The research objective was to record bird species and analyze their presence in the wetlands. Diurnal birds were observed from 07.00-10.00 and 15.00-18.00 on three sites consisting of swamps, paddy fields, and rubber plantations in January 2023. Observers walked two kilometers back and forth for three times on each site. Thirty species (22 families) of birds were found and only 3 species were categorized as water birds. Most of these birds are of least concerned and are not protected. The degree of similarity between bird communities between sites ranged from 0.31 to 0.36. The level of similarity is likely to increase if the observations are made with a greater number of repetitions